PENERAPAN GOOD CORPORATE GOVERNANCE “UPAYA MEREDUKSI POTENSI KONFLIK DALAM PERUSAHAAN” - Abdullah Abdullah (AkMen JURNAL ILMIAH, 2009)
One of best effort to lessen intracorporate conflict is by applying principle Good Corporate Governance. Principles GCG is: Transparancy, Accountability, Responsibility, Independency, and Fairness. Power and Kewenangan for Direksi to apply principle Good Coorporate Governance at company is a a real acurate thing is applied to remembers very susceptible companys with conflict, either conflict steming from within and also Konflik with outside party. Party sides that is having foe ordinary is owner with the shareholders, between minority stockholders with majority shareholder, and between companies with Stakeholders (Employees, client, cutomer, etc). Applying aspect is more in the form of inforcement various law and regulations, internal regulation and standard industry applied and guidance of behavior of organization ( Ethics, etc). this regulation and rule is bottom " order plays at" which may not be impinged in executing management of organization. organizational also is an dynamic entity, especially for organization of business, therefore need to strive best (best practices) to yield prunes performance.